Incidental disgust does not cause moral condemnation of neutral actions - Jussi Jylkkä; Johanna Härkönen; Jukka Hyönä (Routledge, 2022)
Emotivism in moral psychology holds that making moral judgements is at least partly an affective process. Three emotivist hypotheses can be distinguished: the elicitation hypothesis (that moral transgressions elicit emotions); the amplification hypothesis (that disgust amplifies moral judgments); and the moralisation hypothesis (that affect moralises the non-moral). Even though the moralisation hypothesis is the strongest and most radical form of emotivism, it has not been systematically experimentally tested. Most previous studies have used as stimuli morally wrong actions, and thus they cannot answer whether disgust is sufficient to moralise an otherwise neutral action. In Experiment 1 (N = 87) we tested the effect of incidental disgust on morally neutral scenarios, and in Experiment 2 (N = 510) the differential effect of disgust on neutral and wrong scenarios. The results did not support either the moralisation or the amplification hypothesis. Instead, Bayesian analyses provided substantial evidence for the null hypothesis that incidental disgust does not affect moral ratings. The results are in line with a recent meta-analysis suggesting that disgust has no effect on moral ratings.